Suitable conditions for natural regeneration in variable retention harvesting of southern Patagonian Nothofagus pumilio forests - Toro Manríquez, Mónica D.R.; Cellini, Juan Manuel; Lencinas, María Vanessa; Peri, Pablo Luis; Peña Rojas, Karen A.; Martínez Pastur, Guillermo José (SpringerOpen, 2019)
Background: Variable retention (aggregated and dispersed retention) harvesting proposed for Nothofagus pumilio was designed for timber purposes and biodiversity conservation. Harvesting by opening canopy generates different microenvironments and creates contrasting conditions for seedling establishment, growth, and eco-physiology performance due to synergies (positives or negatives) with biotic and abiotic factors. This study evaluated the regeneration in different microenvironment conditions within managed stands during 5 years after harvesting. Remnant forest structure after harvesting and different microenvironments were characterized in managed stands, where 105 regeneration plots were measured (3 stands × 7 microenvironments × 5 replicas). We characterized the seedling bank, as well as growth and ecophysiology performance of the regeneration. Univariate and multivariate analyses were conducted for the comparisons. Results: Microenvironments offered different environmental conditions for natural regeneration (soil moisture and light availability). Seedling under debris and dicot plants showed better eco-physiological performance, establishment, and growth than plants growing under monocots or located in the dispersed retention without the protection of other understory plants. The most unfavorable microenvironment conditions were high canopy cover of remnant trees (inside the aggregates or close to trees in the dispersed retention) and heavily impacted areas (skidder extraction roads). Conclusions: Favorable microenvironments in the harvested areas will improve the natural recruitment, growth, and eco-physiology performance of the natural regeneration after harvesting. It is necessary to develop new silvicultural practices that decrease the unfavorable microenvironments (e.g., road density or excessive woody accumulation), to assure the success of the proposed silvicultural method.